2020
DOI: 10.1038/s41598-020-66332-y
|View full text |Cite
|
Sign up to set email alerts
|

Anodal block permits directional vagus nerve stimulation

Abstract: Threshold-intensity (122 trains) Supra-threshold intensity (75 trains) C. caud. C. ceph. Pol. diff. C. caud. C. ceph. Pol. diff.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
58
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 66 publications
5
58
1
Order By: Relevance
“…It is worth noting that A-fiber amplitude in these experiments reflects activation of both efferent and afferent A-fibers, which convey sensory information from the lungs. In our experiments, the recording electrode was placed caudally to the stimulating electrode and the stimuli were delivered in the cathodecaudad polarity, promoting the activation of efferent fibers [43]. Using this configuration, it is likely that a significant part of the Afiber component corresponds to activation of efferent A-fibers, as some of the afferent A-fiber activity is blocked by the hyperpolarizing anode [43].…”
Section: Vns Evoked Fiber Activity and Physiological Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that A-fiber amplitude in these experiments reflects activation of both efferent and afferent A-fibers, which convey sensory information from the lungs. In our experiments, the recording electrode was placed caudally to the stimulating electrode and the stimuli were delivered in the cathodecaudad polarity, promoting the activation of efferent fibers [43]. Using this configuration, it is likely that a significant part of the Afiber component corresponds to activation of efferent A-fibers, as some of the afferent A-fiber activity is blocked by the hyperpolarizing anode [43].…”
Section: Vns Evoked Fiber Activity and Physiological Responsesmentioning
confidence: 99%
“…In our experiments, the recording electrode was placed caudally to the stimulating electrode and the stimuli were delivered in the cathodecaudad polarity, promoting the activation of efferent fibers [43]. Using this configuration, it is likely that a significant part of the Afiber component corresponds to activation of efferent A-fibers, as some of the afferent A-fiber activity is blocked by the hyperpolarizing anode [43]. This would explain the relatively strong linear relationship between A-fiber amplitude and EMG activity, and the weaker relationship with changes in breathing (Fig.…”
Section: Vns Evoked Fiber Activity and Physiological Responsesmentioning
confidence: 99%
“…By recording evoked compound action potentials through a second implanted nanoclip on the same nerve, they showed that current-steered stimulation modulated songbird vocalizations more precisely than bulk stimulation, and that different spatial patterns of stimulation reliably activated different subsets of nerve fibers. This is important because many peripheral nerves, such as the vagus nerve, contain several different calibers and types of fibers, each associated with different physiological functions (Ahmed et al 2020 ). Therefore, the ability to achieve fiber-specificity through patterned neurostimulation works to maximize desired end-organ specific changes, while minimizing potential off-target side effects.…”
Section: Main Textmentioning
confidence: 99%
“…Knowledge of threshold intensities is essential in neuromodulation studies and therapies. The threshold for a given stimulation modality varies widely across subjects 16, 17 . Mechanisms that determine threshold can be grouped into 3 categories: those related to the neural interface, those related to the generated electrical field, and those related to the physiological status of the end-organ.…”
Section: Introductionmentioning
confidence: 99%
“…Factors that determine the neural interface include surgical technique 2, 11 , foreign body response to a long-term implanted electrode 1, 8 19 , and degradation of the electrode itself 20 . Factors influencing the generated electrical field include electrode geometry 21 22 , electrode orientation relative to the stimulated neural elements 17, 21, 23 , and stimulation parameters 11, 21 . Finally, the state of a subject or the end-organ at the time of stimulation affects the stimulation threshold 24 .…”
Section: Introductionmentioning
confidence: 99%